A Systematic Review to Assess the Relationship between Disseminated Cerebral Aspergillosis, Leukemias and Lymphomas, and Their Respective Therapeutics - Brianne N. Sullivan; Mia A. Baggett; Samantha S. O’Connell; Keith M. Pickett; Chad Steele (Journal of Fungi, 2022)
Disseminated disease following invasive pulmonary aspergillosis (IPA) remains a significant contributor to mortality amongst patients with hematologic malignancies (HMs). At the highest risk of mortality are those with disseminated disease to the central nervous system, known as cerebral aspergillosis (CA). However, little is known about the risk factors contributing to disease amongst HM patients. A systematic review using PRISMA guidelines was undertaken to define HM patient subgroups, preventative measures, therapeutic interventions, and outcomes of patients with disseminated CA following IPA. The review resulted in the identification of 761 records, of which 596 articles were screened, with the final inclusion of 47 studies and 76 total patients. From included articles, the proportion of CA was assessed amongst HM patient subgroups. Further, pre-and post-infection characteristics, fungal species, and mortality were evaluated for the total population included and HM patient subgroups. Patients with acute myeloid leukemia and acute lymphoid lymphoma, patients receiving corticosteroids as a part of their HM therapeutic regimen, and anti-fungal prophylaxis constitute the top identified patient populations at risk for disseminated CA. Overall, information presented here indicates that measures for the prevention of IPA should be taken in higher-risk HM patient subgroups. Specifically, the type of anti-fungal therapy used should be carefully considered for those patients with IPA and increased risk for cerebral dissemination. Additional reports detailing patient characteristics are needed to define further the risk of developing disseminated CA from IPA in patients with HMs.